Comparing the effectiveness of schema therapy and acceptance and commitment therapy on chronic fatigue syndrome in patients with multiple sclerosis - Nazari, Abbas; Saedi, Sara; Abdi, Mansour (Journal of Personality and Psychosomatic Research (JPPR), 2023)
This study aimed to compare the effectiveness of schema therapy and acceptance and commitment therapy on chronic fatigue syndrome in patients with multiple sclerosis. The research design was quasi-experimental with a pre-test-post-test design with two experimental groups and, one control group and a one-month follow-up phase. The statistical population of the present study included all the patients with multiple sclerosis in Markazi Province in 2021. This research selected the statistical sample size of 45 people by available sampling. It included 3 groups of 15 people, including treatment groups based on commitment and acceptance, schema therapy and control group. For both experimental groups, the relevant therapeutic intervention was held in 120-minute sessions once a week. In contrast, the people in the control group did not receive the aforementioned therapeutic intervention. Chalder et al.’s (1993) Chronic Fatigue Scale was used to collect data. In order to statistically analyze the data, analysis of covariance test and SPSS software were used. The statistical analysis of the data showed that the implementation of the schema therapy approach on chronic fatigue was insignificant. However, the acceptance and commitment approach had a significant effect on reducing chronic fatigue scores. Also, comparing the effect of two therapeutic approaches showed significant differences between the effectiveness of two therapeutic approaches, schema therapy and acceptance and commitment therapy, on chronic fatigue syndrome. The results indicate that the therapeutic approach based on acceptance and commitment has more effects on reducing chronic fatigue symptoms than schema therapy.